Criteria for success of the organizational culture of the department of a higher educational establishment - Synhaivska, Iryna; Apisheva, Aminet; Сингаївська, Ірина Валентинівна; Апішева, Амінет Шабанівна; Апішева, Амінет (Scientific Center of Innovative Researches OÜ, 2020)
The article discusses outstanding characteristics of the organizational culture of the department of a higher-educational institution based on employees’ ideas about existing and desired organizational culture with the goal to increase the department’s successfulness. The ideas about a preferred state can be used for planning the further development of the department’s organizational culture. Criteria for successfulness of department’s organizational culture are determined by both internal and external factors. The external criterion for the assessment of successfulness of department’s activity is represented by objective effectiveness of the quality of student training, which is included into department’s rating and reflects successfulness of psychological and pedagogical interaction between the teaching staff and the students. It is suggested to use “objective effectiveness” as a criterion for the assessment of department’s organizational culture successfulness. Also, the necessity of taking into consideration the directions of specialist training while planning the development of organizational culture of the department. The article also presents the analysis of the internal criterion for the successfulness of the department’s organizational culture, which is determined by the degree of discrepancy between the employees’ ideas about existing and preferred organizational culture. High divergence degree causes socio-psychological internal tension among coworkers. We consider such an organizational culture to be unfavorable, and therefore unsuccessful. It is suggested to use organizational culture “favourability” as a criterion for successfulness. It has been clarified that the correct OCAI methodology usage requires preliminary application of statistical criteria for checking normality of the source data distribution
Keywords: organizational culture of the department of a higher-educational institutiones; successfulness criterion for the organizational culture of the department of a higher-educational institution; socio-psychological tension among employe